Effectiveness of Environmental Change Learning Tools Based on STEM-PjBL Towards 4C Skills of Students - Triana, Dwita; Ulung Anggraito, Yustinus; Ridlo, Saiful (Journal of Innovative Science Education, 2020)
Skills that must be possessed in the 21st century include critical thinking and problem solving, creativity and innovative skills, collaboration and communication skills (4C) in order to be able to survive and compete globally. This study aims to analyze the effectiveness of environmental change learning tools based on STEM-PjBL including syllabus, lesson plans, teaching materials, student worksheets and evaluation tools on students' 4C skills. The learning model used in this study is Project Based Learning (PjBL). The study was conducted at SMA Negeri 4 Medan and SMA Negeri 16 Medan class X. Samples were taken using a purposive sampling method consisting of 4 classes with a total of 126 students. This research uses quantitative research methods with one group pretest-posttest design. The results showed the implementation of learning activities based on the activities of teachers obtained a score of 0.915 with a very good category. Furthermore, critical thinking and problem solving skills get an average score of N-Gain 0.587 with the medium category, creativity and innovative skills get an average score of 0.809, collaboration skills score 0.816 and communication skills score 0.825 with all categories very good. These results indicate that environmental change learning tools based on STEM-PjBL is effective against students' 4C skills.